IECON 2010 - 36th Annual Conference on IEEE Industrial Electronics Society 2010
DOI: 10.1109/iecon.2010.5675110
|View full text |Cite
|
Sign up to set email alerts
|

Integrated modeling of nonlinear dynamics and contact mechanics of electrostatically actuated RF-MEMS switches

Abstract: In this work, a novel nonlinear dynamic model is developed to investigate the bouncing and deformation behaviors of an electrostatically actuated, ohmic-contact RF-MEMS switch. The model accounts for a real geometry, the electrostatic actuation, squeeze-film damping effect, and the nonlinear elastic-plastic contact mechanics using Hertz theory. A lowcomplexity formulation based on finite differential analysis is employed to solve the model equations in the time-domain. The proposed methodology is validated usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The FETD method is popular in the MEMS field using commercial software, such as RF switches using ANSYS [39,40,193] and COMSOL Multiphysics [164]. The FDTD method has also been used in studying the time-dependent behavior of switches [37,155,[159][160][161][162] and tapping-mode AFM [148,149]. However, both methods require extensive time integration of second-order ODEs, making themselves computationally expensive and nearly impossible for systematic investigation and device optimization.…”
Section: Finite Difference Methods and Finite Element Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FETD method is popular in the MEMS field using commercial software, such as RF switches using ANSYS [39,40,193] and COMSOL Multiphysics [164]. The FDTD method has also been used in studying the time-dependent behavior of switches [37,155,[159][160][161][162] and tapping-mode AFM [148,149]. However, both methods require extensive time integration of second-order ODEs, making themselves computationally expensive and nearly impossible for systematic investigation and device optimization.…”
Section: Finite Difference Methods and Finite Element Methodsmentioning
confidence: 99%
“…Distributed-parameter approach is commonly used to analyze MEMS vibro-impact systems that maintains the continuous nature of the structure and represents the response in terms of continuous variables. Based on this approach, MEMS vibro-impact systems are usually modeled as a timevarying, spatially distributed partial differential equation (PDE) coupled with the nonlinear terms and most of them are based on the Euler-Bernoulli theory [18,37,115,117,141,148,149,160,163]. A widely used method to treat these PDEs is to reduce them to tractable ordinary differential equations (ODEs) through modal analysis [18,115,117,141,163], resulting in a lumped reduced-order model.…”
Section: Techniques For Obtaining the Dynamical Behaviorsmentioning
confidence: 99%
“…Forcing Dynamics Damping Impact Adhesion Experimentally validated Wang et al [6] ES L SF Asperity -Threshold for bouncing Decuzzi et al [7] ES D SF VdW VdW -Do et al [8] ES D SF Elastic/plastic -Periods of contact Park et al [9] ES suggested novel impact/bounce models over various substrate conditions, which are used to inform the lumped-parameter modeling in this paper. Additionally, for models based on an assumption that the geometry of the contact surfaces is well known, close estimation of the short-ranged forces was conducted in several studies, including use of the Reynolds equation for squeeze-film damping [3,6,7,10,11] and various adhesion/contact force models such as Johnson-Kendall-Roberts (JKR) [3] or Lennard-Jones force [12].…”
Section: Authorsmentioning
confidence: 99%
“…This is especially true for studies of scanning probe technologies, as in atomic force microscopy [1] or probe storage research [2], which has allowed extremely detailed studies of contact dynamics for such instruments. For applications with larger interacting surfaces, on the order of 10-1000 μm, the most prevalent area of contact modeling is for micro-electromechanical switches [3,[6][7][8][9][10][11][12][13], with additional work being done on certain vibration scavenging [4] or miniature gear devices [5]. Table 1 shows a summary of many contact models from the literature for interacting surfaces at this scale.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation